1997
DOI: 10.1039/a704615d
|View full text |Cite
|
Sign up to set email alerts
|

Antitumour Heterocycles. Part 16.1 The Synthesis of 7,10-Dimethoxyellipticine and its Pyrrolo[2,3-f]carbazole and Pyrrolo[3,2-f] Analogues

Abstract: The final examples in our ellipticine/pyrrolocarbazole synthesis programme are 7,10-dimethoxyellipticine 1a and the corresponding pyrrolocarbazoles 2a and 3a which have been synthesised from 4,6-dimethoxyindole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…883 In 1997, Shannon and his group observed the formation of a N-C3-linked dimer during the transformation of a 3-bromocarbazole to a 3-cyanocarbazole by reaction with copper(I) cyanide in N,N-dimethylformamide under reflux. 884 However, this procedure was not applied to the synthesis of naturally occurring dimeric carbazoles. Additional total syntheses of dimeric carbazole alkaloids are described in section XI.6.…”
Section: Total Synthesis Of (±)-Bismurrayaquinone-a By Bromoquinone-e...mentioning
confidence: 99%
See 1 more Smart Citation
“…883 In 1997, Shannon and his group observed the formation of a N-C3-linked dimer during the transformation of a 3-bromocarbazole to a 3-cyanocarbazole by reaction with copper(I) cyanide in N,N-dimethylformamide under reflux. 884 However, this procedure was not applied to the synthesis of naturally occurring dimeric carbazoles. Additional total syntheses of dimeric carbazole alkaloids are described in section XI.6.…”
Section: Total Synthesis Of (±)-Bismurrayaquinone-a By Bromoquinone-e...mentioning
confidence: 99%
“…Furukawa and co-workers obtained a mixture of murrafoline-D ( 1230 ), -G ( 1231 ), and -H ( 1232 ) (see Scheme ) by refluxing a solution of murrayafoline-A ( 2 ) and girinimbine ( 458 ) in aqueous methanol for 27 h in the presence of ion-exchange resin (Nafion 117). , Chakrabarti and Chakraborty described the reaction of girinimbine ( 458 ) with BF 3 etherate in dichloromethane at room temperature, which afforded murrafoline-H ( 1232 ) in 21% yield . In 1997, Shannon and his group observed the formation of a N−C3-linked dimer during the transformation of a 3-bromocarbazole to a 3-cyanocarbazole by reaction with copper(I) cyanide in N , N -dimethylformamide under reflux . However, this procedure was not applied to the synthesis of naturally occurring dimeric carbazoles.…”
Section: Total Synthesis Of (±)-Bismurrayaquinone-a By Bromoquinone-e...mentioning
confidence: 99%
“…Both the Ullmann reaction (copper-catalyzed N -arylation of amines) and the related Goldberg reaction (copper-catalyzed N -arylation of amides) predate the palladium-catalyzed amination methodology by many decades. While applications of the Ullmann and Goldberg reactions in academic and industrial laboratories are well-documented, the methods have remained relatively undeveloped.…”
Section: Introductionmentioning
confidence: 99%
“…In a preliminary paper on the Goldberg coupling reaction of aryl halides with amides, the effect of a variety of substituents in the reactants was investigated and it was shown that the yields are markedly susceptible to the presence of electron withdrawing groups in both reactants. 1 The effect of substituent methyl groups on the reaction yield was not investigated but this could be important if the products such as 1 or 2 were to be used for the synthesis of 1,4dimethylcarbazoles 3 (Scheme 1) as precursors of ellipticines. Until now, carbazoles have been fruitful precursors of ellipticines.…”
mentioning
confidence: 99%
“…We now report the synthesis of a series of multisubstituted diphenylacetamides 1 and diphenylsulfonamides 2 which embody 2,5-dimethyl substituents, thus extending our earlier work. 1 The diphenylacetamides (1a-f) were prepared by Goldberg coupling, as shown in the Table 1. The different effect of substituents in the coupling components on the yields obtained is noteworthy (16-81%).…”
mentioning
confidence: 99%